Ultrasmall gold nanosatellite-bearing transformable hybrid nanoparticles for deep tumor penetration. (1st October 2018) - Son, Soyoung; Deepagan, Veerasikku G.; Shin, Sol; Ko, Hyewon; Min, Jiwoong; Um, Wooram; Jeon, Jueun; Kwon, Seunglee; Lee, Eun Sook; Suh, Minah; Lee, Doo Sung; Park, Jae Hyung
Graphical abstract: Abstract: Since delivering drugs to an entire tumoral region leads to high therapeutic efficacy and good prognosis, achieving deep tumoral penetration of drugs is a major issue in cancer treatment. In this regard, conventional nanomedicines (>50 nm) have shown limitations in cancer therapy, primarily attributed to the heterogeneous distribution of drugs because of the physiological barrier of the tumor interstitial space. To address this issue, we prepared transformable hybrid nanoparticles (TNPs) consisting of a pH-responsive nanocarrier (PEG-PBAE) and doxorubicin (DOX)-conjugated ultrasmall (<3 nm) gold nanoparticles (nanosatellites). It has been shown that PEG-PBAE can serve as a reservoir for nanosatellites and release them in mildly acidic conditions (pH 6.5), mimicking the tumor microenvironment. When DOX-loaded TNPs (DOX-TNPs) were intravenously injected into tumor-bearing mice, they successfully accumulated and dissociated at the extracellular level of the tumor, leading to the disclosure of nanosatellites and free DOX. While the free DOX accumulated in tumor tissue near blood vessels, the deeply diffused nanosatellites were taken up by the tumor cell, followed by the release of DOX via cleavage of pH-responsive ester linkages in the nanosatellites at the intracellular level. Consequently, the DOX-TNPs effectively suppressed tumor growth through improved tumor penetration of DOX, suggesting their promising potential as a cancer nanomedicine. Statement of Significance: Deep tumor penetration of anticancer drug is an important issue for high therapeutic efficacy. If the drugs cannot reach cancer cells in a sufficient concentration, their effectiveness will be limited. In this regard, conventional nanomedicine showed only modest therapeutic efficacy since they cannot deliver their payloads to the deep site of tumor tissue. This heterogeneous distribution of the drug is primarily attributed to the physiological barriers of the tumor microenvironment, including a dense extracellular matrix. To surmount this challenge, we developed tumor acidity-triggered transformable nanoparticles. By encapsulating doxorubicin-conjugated ultrasmall gold nanosatellites into the nanoparticles, the drug was not significantly bound to genetic materials, resulting in its minimal sequestration near the vasculature and deep tumor penetration. Our strategy could resolve not only the poor penetration issue of the drug but also its restricted tumor accumulation, suggesting the potential as an effective nanotherapeutics.